2009
DOI: 10.1080/15398280903340798
|View full text |Cite
|
Sign up to set email alerts
|

Quality Health Information on the Internet: Developing a Diabetes Pathfinder for the Chinese Population

Abstract: A Web-based bilingual diabetes information pathfinder was created to help the Chinese population access quality health information on the Internet as part of a collaborative outreach project in the Dallas-Fort Worth area. A survey was conducted to identify the demographics, Internet usage, health information needs, and preferences for training sessions of the Chinese population. Breast cancer, diabetes, and breast cancer were the top three diseases of interest. The process of developing the pathfinder is descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The main and most trusted source of diabetes information for the elderly with pre-diabetes in rural areas was doctors, which was similar to the previous studies 15–18. In addition, some previous research has found that family members,19 neighbours,20 magazines,21 television21 and the internet22 23 were the sources of health or disease information as much for the elderly as for other groups. As technology advances, it is becoming more and more common for individuals to use the internet or mobile phones to search for relevant health information.…”
Section: Discussionmentioning
confidence: 99%
“…The main and most trusted source of diabetes information for the elderly with pre-diabetes in rural areas was doctors, which was similar to the previous studies 15–18. In addition, some previous research has found that family members,19 neighbours,20 magazines,21 television21 and the internet22 23 were the sources of health or disease information as much for the elderly as for other groups. As technology advances, it is becoming more and more common for individuals to use the internet or mobile phones to search for relevant health information.…”
Section: Discussionmentioning
confidence: 99%